Model‐based evaluation of pulmonary pharmacokinetics in asthmatic and COPD patients after oral olodaterol inhalation. (23rd June 2016) - Borghardt, Jens Markus; Weber, Benjamin; Staab, Alexander; Kunz, Christina; Kloft, Charlotte
Abstract : Aims: Olodaterol is an orally inhaled β2 ‐agonist for treatment of chronic obstructive pulmonary disease (COPD). The aims of this population pharmacokinetic (PK) analysis were: (1) to investigate systemic PK and thereby make inferences about pulmonary PK in asthmatic patients, COPD patients and healthy volunteers, and (2) to assess whether differences in pulmonary efficacy might be expected based on pulmonary PK characteristics. Methods: Plasma and urine data after olodaterol inhalation were available from six clinical trials comprising 710 patients and healthy volunteers (single and multiple dosing). To investigate the relevance of covariates, full fixed‐effect modelling was applied based on a previously developed healthy volunteer systemic disposition model. Results: A pulmonary model with three parallel absorption processes best described PK after inhalation in patients. The pulmonary bioavailable fraction (PBIO) was 48.7% (46.1–51.3%, 95% confidence interval) in asthma, and 53.6% (51.1–56.2%) in COPD. In asthma 87.2% (85.4–88.8%) of PBIO was slowly absorbed with an absorption half‐life of 18.5 h (16.3–21.4 h), whereas in COPD 80.1% (78.0–82.2%) was absorbed with a half‐life of 37.8 h (31.1–47.8 h). In healthy volunteers absorption was faster, with a half‐life of 18.5 h (16.3–21.4 h) of the slowest absorbed process, which characterized 74.6% (69.1–80.2%) of PBIO. Conclusions: The modelling approach successfully described data after olodaterol inhalation in patients and healthy volunteers. Slow pulmonary absorption was demonstrated both in asthma and COPD. Absorption characteristics after olodaterol inhalation indicated even more beneficial lung targeting in patients compared to healthy volunteers.